Estimation and Comparison between Cost Efficiency and Economies of Scale of Banking Sector in China - Song, Haojie (2019)
Cost efficiency can help managers to take corresponding strategies in time, and also beneficial for investors to study the bank’s advantages. On the other hand, economies of scale can provide the decision-making basis for whether the management should continue to expand. So, it is necessary and reasonable to pay great attention to cost efficiency and scale efficiency. Based on this, this paper uses stochastic frontier analysis to analyze and compare the cost efficiency and economies of scale of China's banking industry. 180 banks from 2012 to 2018, including state-owned banks, large joint-stock banks, city commercial banks, rural commercial banks and foreign banks, are covered in the sample. In the course of regressing, M3T test and Likelihood Ratio test give strong support to the right skewness and existence of composed error term uit + vit. To sum up, some conclusions are drawn that: the overall average cost efficiency of the sample banks is very high, reaching 0.9157747; by types, the cost efficiency of foreign banks, on the whole, is lower than that of other types of banks; local banks, by contrast, are generally equally cost efficient, generally staying above 0.9; sample banks achieve less economies of scale overall (overall economies of scale are less than 1); only foreign banks have realized scale economy on the whole, while the values of scale economy for other types of banks have not exceeded 1.